Production of Neisseria meningitidis Transferrin-Binding Protein B by Recombinant Bordetella pertussis - Coppens, Isabelle (American Society for Microbiology, 2001)
Neisseria meningitidis serogroup B infections are among the major causes of fulminant septicemia and meningitis, especially severe in young children, and no broad vaccine is available yet. Because of poor immunogenicity of the serogroup B capsule, many efforts are now devoted to the identification of protective protein antigens. Among those are PorA and, more recently, transferrin-binding protein B (TbpB). In this study, TbpB of N. meningitidis was genetically fused to the N-terminal domain of the Bordetella pertussis filamentous hemagglutinin (FHA), and the fha-tbpB hybrid gene was expressed in B. pertussis either as a plasmid-borne gene or as a single copy inserted into the chromosome. The hybrid protein was efficiently secreted by the recombinant strains, despite its large size, and was recognized by both anti-FHA and anti-TbpB antibodies. A single intranasal administration of recombinant virulent or pertussis-toxin-deficient, attenuated B. pertussis to mice resulted in the production of antigen-specific systemic immunoglobulin G (IgG), as well as local IgG and IgA. The anti-TbpB serum antibodies were of the IgG1, IgG2a, and IgG2b isotypes and were found to express complement-mediated bactericidal activity against N. meningitidis. These observations indicate that recombinant B. pertussis may be a promising vector for the development of a mucosal vaccine against serogroup B meningococci.